Using evidence in health promotion in local government: contextual realities and opportunities. (21st March 2013) - Pettman, Tahna Lee; Armstrong, Rebecca; Pollard, Ben; Evans, Rachel; Stirrat, Amanda; Scott, Isha; Davies‐Jackson, Georgia; Waters, Elizabeth
Abstract : Issue addressed: New national and state preventive health investments have provided significant funding for local governments (LGs) to be involved in planning and implementing health promotion interventions. There is an expectation that this work is evidence based; however, inadequate support and systems exist for evidence‐informed planning and decision making in LGs. Previous initiatives have aimed to build capacity and leadership in LG health promotion, but the training, support and infrastructure have been sporadic. Methods: Across 2009–11 we implemented a National Health and Medical Research Council of Australia (NHMRC)‐funded university‐LG research project to explore the feasibility, usefulness and outcomes of a knowledge translation (KT) intervention to increase the use of evidence in LGs. Within this exploratory cluster randomised controlled trial, one strategy being evaluated was workforce capacity building, during which group discussions revealed contextual challenges in delivering evidence‐informed health promotion within the current funding context. Discussion was recorded. The group acknowledged the need to identify barriers and realistic practical solutions, and to communicate these more broadly. Results: Barriers to sourcing and applying evidence to inform health promotion emerged from discussions with LG representatives. System‐level contextual factors affecting decisions were also discussed, namely concerns about organisational capacity and 'culture' to plan, implement and evaluate effective initiatives in LGs. Possible solutions suggested included: systems for access to academic literature; processes that make it easier to use evidence; training in evidence‐informed health promotion to build organisational culture and capacity; and research‐practice partnerships and mentoring. Conclusions: Targeted strategies with individuals (LG staff) and organisations (leadership, systems) are needed to realise the potential of current health promotion investments. Research‐practice partnerships are likely to be important. It seems obvious that it is impossible to be evidence informed without mechanisms to access and apply evidence. We invite other LGs to reflect upon their experiences in such initiatives, and to consider whether the strategies we propose may be useful. So what?: The increased emphasis on health promotion and non‐communicable disease prevention programs may be limited by the capacity, confidence and organisational culture to inform policies and programs with best‐available evidence. We describe some of the current challenges and contextual factors as they are being experienced. There are opportunities for national and state governments, organisations representing local government (e.g. municipal associations) and research partners to provide targeted support to councils. This may assist in achieving effective health promotion at the community level. Abstract : Health promotion initiatives in local governments may be limited by the capacity, confidence and organisational culture to use best available evidence. This paper describes some of the current challenges and contextual factors as they are being experienced. There are opportunities for national and state governments, organisations representing local government (e.g. municipal associations) and research partners to provide targeted support to councils. This may assist in achieving effective health promotion at the community level.